Aspectos do grotesco na poesia de João Cabral de Melo Neto - Zênia de Faria (Estudos de Literatura Brasileira Contemporânea)
This paper aims to analyse some poems of João Cabral de Melo Neto in the light of some theories of the grotesque, particularly those of Bakhtin and Kayser, trying to point out the presence of this “negative category” in the work of this poet.